An Act to prevent and punish the sale of Arms and Ammunitions to Indians, Sec. 1., in The Compiled Laws of the Territory of Arizona 99 (John P. Hoyt ed., 1877) - (:unkn) unknown (General Publisher, 1868)
Prohibited the sale or giving of arms or ammunition to "any Indians", or repair of their arms. Violators fined fifty dollars on first offense with costs, subsequent offenses fined not less than one hundred dollars with costs and imprisoned for thirty days.
--
Keywords: TRANSFER - DANGEROUS PERSONS